Tinjauan Konsumerisme dalam Trend Arisan Online - Ignatius Aji Dwiatmaja; Muhammad Imam Alfikri; Irfan Khairan Ali (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2024)
Online arisan is a phenomenon where people organize and participate in arisan (rotating savings and credit associations) through online platforms. In online arisan, consumerism can have diverse impacts depending on the values and behaviors adopted by the participants. Factors that can influence consumerism in online arisan include the choice of prizes, the use of technology and social media, as well as the convenience and flexibility offered by online arisan. Although there is potential for more dominant consumerism, there are still arisan groups that maintain their traditional values.